2015
DOI: 10.1021/ml5004684
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure–Activity Relationship Study of 1-Phenyl-1-(quinazolin-4-yl)ethanols as Anticancer Agents

Abstract: A quinazoline derivative PVHD121 (1a) was shown to have strong antiproliferative activity against various tumor-derived cell lines, including A549 (lung), NCI-H460 (lung), HCT116 (colon), MCF7 (breast), PC3 (prostate), and HeLa (cervical) cells with IC 50 values from 0.1 to 0.3 μM. A structure−activity relationship (SAR) study at the 2-and 4-position of the quinazoline core lead to the discovery of more potent anticancer agents (14, 16, 17, 19, 24, and 31). The results of an in vitro tubulin polymerization ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 20 publications
2
20
0
Order By: Relevance
“…1A) and its fluorescent derivative 1-(4-methoxyphenyl)-1-(2morpholinoquinazolin-4-yl)ethan-1-ol (PVHD277) ( Fig. 6A) had submicromolar anti-cell proliferative EC 50 values in various tumor-derived cell lines (Suzuki et al, 1998(Suzuki et al, , 2017Kuroiwa et al, 2015). We also showed that they directly bound to the colchicine site of tubulin and inhibited tubulin polymerization in vitro (Kuroiwa et al, 2015).…”
Section: Introductionmentioning
confidence: 80%
“…1A) and its fluorescent derivative 1-(4-methoxyphenyl)-1-(2morpholinoquinazolin-4-yl)ethan-1-ol (PVHD277) ( Fig. 6A) had submicromolar anti-cell proliferative EC 50 values in various tumor-derived cell lines (Suzuki et al, 1998(Suzuki et al, , 2017Kuroiwa et al, 2015). We also showed that they directly bound to the colchicine site of tubulin and inhibited tubulin polymerization in vitro (Kuroiwa et al, 2015).…”
Section: Introductionmentioning
confidence: 80%
“…In addition to developing a novel anticancer drug, a series of compounds with various substituents at positions 2 and 4 of the quinazoline core were synthesized and evaluated for anticancer activities. 67 Structure-activity relationship studies suggested that the 2-chloroquinazoline derivative compound 16 was the most potent and most active compound of the series (Fig. 3) in the low micromolar range.…”
Section: Quinazoline Derivatives As Tubulin Polymerization Inhibitorsmentioning
confidence: 97%
“…A data set of 45 quinazoline-based anticancer agents was collected [10] . Reported activity values (IC 50 ) of inhibitors were converted into pIC 50 values for 3D-QSAR analysis.…”
Section: Data Setmentioning
confidence: 99%
“…Recently, quinazoline-based anticancer agents were reported [10] . However, a three-dimensional quantitative structure-activity relationship (3D-QSAR) analysis on these inhibitors has not been performed to establish exactly how their chemical structures relate to the inhibitory activities.…”
Section: Introductionmentioning
confidence: 99%